Patient Reported Determinants of Health: A Qualitative Analysis of Veterans with Chronic Obstructive Pulmonary Disease. (1st June 2013) - Panos, Ralph J.; Krywkowski-Mohn, Sara M.; Sherman, Susan N.; Lach, Laura A.
Abstract: Although COPD is a common disorder of veterans who receive care from the Veterans Healthcare Administration (VHA), the perceptions of veterans with COPD about their disease, its effects on their lives, and their interactions with the VHA have not been determined. Utilizing qualitative methodology, we conducted focus groups of veterans with COPD at the Cincinnati VA Medical Center. Participants were selected by systematic sampling from the top quintile of veterans stratified by the cost of healthcare utilization related to a primary diagnosis of COPD and grouped by age and use of supplemental oxygen. All 42 participants were male and had a mean age of 65 years. Analysis of the focus group transcripts demonstrated five major themes: 1) Physical and Functional Limitations: work and employment constraints, recreation restrictions, limits on activities of daily living, reduced sexuality, concerns about housing and finances, and physical symptoms; 2) Restricted Social Interactions/Altered Social Networks: altered relationships with friends and family and reliance upon family and care givers; 3) Emotional Effects: reduced self-worth, vulnerability, depression, perseverance and adaptation, hopelessness, fear, pride, and lack of control; 4) Limitations in the Understanding of COPD: unawareness of diagnosis, triggers and reaction to disease manifestations, COPD management; and 5) Complex Healthcare Interactions. COPD pervasively and extensively affects all aspects of veterans' lives and causes significant consequences for their care and management.